PEMETAAN LOKASI POTENSI DESA WISATA DI KABUPATEN SLEMAN TAHUN 2015 - Anggara Setyabawana Putra; Akhmad Fauzy (Asian Journal of Innovation and Entrepreneurship, 2015)
These last few years , a lot of tourism village appeared in various regions , as well as in Sleman , Yogyakarta. Department of Tourism and Culture Sleman , noted , until 2015 there were a total of 35 tourism village with a variety of categories . With many of the tourism village , is necessary to manage the tourism village well . Mapping the location of the tourism village in Sleman district , conducted to provide ease of access roads to tourist sites for tourists domestic and foreign tourists . Software used is ArcGIS 10.1 . with ArcGIS can make a map of Tourism Village Location Sleman 2015. Keywords: Tourism Village , Maps , ArcGIS.